2016
DOI: 10.1093/hsw/hlw059
|View full text |Cite
|
Sign up to set email alerts
|

The Complex Interplay of Adverse Childhood Experiences, Race, and Income

Abstract: An extensive research base shows evidence of racial disparities in health outcomes, and a growing body of evidence points to associations between adverse childhood experiences (ACEs) and poor health. This study uses data from the 2011 and 2012 Wisconsin Behavioral Risk Factor Surveillance System surveys to identify the relative contributions of ACEs, race, and adult income to predicting three sets of adverse adult health outcomes. The authors found that controlling for demographic factors, ACEs strongly predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 26 publications
2
19
0
Order By: Relevance
“…The authors found that Black race is marginally associated with poor general health, and the relationship was weakened when controlling for ACEs and adult income. This finding suggests that ACEs and adult income may partially mediate the relationship between race and some health outcomes (Slack, Font, & Jones, 2016).…”
Section: Race/gender Differences In Acesmentioning
confidence: 98%
See 1 more Smart Citation
“…The authors found that Black race is marginally associated with poor general health, and the relationship was weakened when controlling for ACEs and adult income. This finding suggests that ACEs and adult income may partially mediate the relationship between race and some health outcomes (Slack, Font, & Jones, 2016).…”
Section: Race/gender Differences In Acesmentioning
confidence: 98%
“…One study utilized a sample of urban minority young adults in Chicago found that 80% of that sample reported at least one ACE as compared to 64% of respondents in the original ACE study (Mersky, Topitzes, & Reynolds, 2013). Similarly, Slack, Font, and Jones (2016) examined how ACEs, race, and adult income predicted adverse health outcomes. The authors found that Black race is marginally associated with poor general health, and the relationship was weakened when controlling for ACEs and adult income.…”
Section: Race/gender Differences In Acesmentioning
confidence: 99%
“…Prior research has consistently found that minority children face cumulative disadvantage, including living in a low-income neighborhood, having a lower family income, and witnessing violence that have negative effects on healthy development (Gerard & Buehler, 2004;Roberts, Gilman, Breslau, Breslau, & Koenen, 2011). In a study by Slack, Font, and Jones (2017), the authors found that race was marginally associated with poor general health, and the relationship was weakened when controlling for ACEs and adult income. Several studies have also examined gender differences in ACE exposure.…”
Section: Race and Gender Effects Of Aces And Mental Health Problemsmentioning
confidence: 99%
“…Deliberately limited to household effects, ACEs exclude important factors taking place outside the home, such as bullying (Lereya et al, 2015) and racial discrimination (Slack et al, 2016). Researchers have therefore proposed amending the original ten measures to include a range of other harmful exposures, such as racism, witnessing community violence, living in an unsafe neighbourhood, bullying, a history of foster care, parental death, food scarcity, parents always arguing, peer rejection, low socioeconomic status, poor academic performance and having no good friends (Finkelhor et al, 2013;Wade et al, 2016).…”
Section: Can Aces Help Us Understand These Effects?mentioning
confidence: 99%